Conocimientos y actitudes en los estudiantes de V y VI semestre de la Carrera de Medicina de la Universidad Técnica de Machala frente el consumo de tabaco. - Jiménez Pinta, Patricia Alejandra (2018)
Consumption of tobacco kills more than seven million people per year worldwide (OMS) and is the main cause of lung cancer, mouth and throat, larynx, esophagus, stomach, kidney, pancreas, liver, bladder, cervix, colon and rectum, and one type of leukemia; The factors that influence are: genetics, home and parental influence, age, depression or other mental illnesses which mainly affects the young population between 21-25 years. The general objective of this research was to determine the knowledge and attitudes of the students of V and VI semester of the Medicine career of the Technical University of Machala against tobacco consumption and the specific ones were to identify the age and sex of the students, to describe the level of knowledge about tobacco consumption, to indicate the attitudes towards tobacco consumption, the study was descriptive-cross-sectional which universe were 104 students, the information was obtained through surveys and the application of the attitude scale, obtaining the following results 79.8% have high knowledge, 18.3% medium and 1.9% low, in terms of attitudes towards tobacco, 80.7% is positive, that is, they are not predisposed to tobacco use and the 19.2% is negative, being susceptible to consume, determining in this way that most students have a high level of knowledge and a positive attitude towards tobacco use which is favorable for the maintenance of health. Keywords: Disease, Death, Problems, Cáncer